PENGARUH MEDIA PROMOSI KESEHATAN JINGLE TERHADAP PENGETAHUAN PENCEGAHAN COVID-19 PADA KELOMPOK MASYARAKAT - Pranata, Fanny Cosla; Winarni, Sri; Rachman, Zainol (Poltekkes Kemenkes Malang, 2022)
Coronaviruses are a large family of viruses that cause disease in humans and respiratory infections, ranging from the common cold to serious illnesses such as Middle East Syndrome and Severe Acute Respiratory Syndrome. Due to the fact that there are still many people who do not comply with the Covid 19 prevention health protocol, the author took the initiative to conduct research on